The Unconditional and Conditional Methods to Examine the Weekend Effect of Stock Returns - ., Suwandi; Kumar, M. Dileep; Muneer, Saqib (International Journal of Economics and Financial Issues, 2015)
This paper examines the weekend effect on stock market returns by using the unconditional method and the conditional method. This paper uses daily closing prices of firms listed in Indonesian stock exchange by using LQ-45 index from January 2006 to December 2013 in three subperiods: All months, non-January months and January month. Independent sample t-test is applied to examine the significance of the weekend effect. Results support the weekend effect in three subperiods by using the unconditional method. But when using the conditional method, the weekend effect only exists in down market for all months period and non-January months period. There's no weekend effect in January month period by using the conditional method, both in up and down market. This paper presents new evidences and supplements the finance literature on the weekend effect for the case in Indonesian stock exchange, and also help investors to develop a good investment strategy. Keywords: Weekend Effect, The Conditional Method, The Unconditional Method, Return of Stock JEL Classifications: E44, G1